Pengaruh Jenis Aktivator Terhadap Penyerapan Ion Logam Pb2+Oleh Kulit Buah Matoa (Pometia pinnata) - Geita Yulyan Firel; Edi Nasra; Indang Dewata; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2023)
The effect of activation types on the biosorpsion of pb2+ metal ions by matoa peel (Pometia pinnata) has been done. The purpose of this study was focused on the effect of the type of activator on the biosorpsion of pb2+ metal ions by the matoa peel (Pometia pinnata) with chemical activation to determine the technical and condition of the activator according to the matoa peel which can be used as a Pb2+ ion biosorbent. The method used is the batch method. The variables in this study were the type of activator and were characterized using the FTIR and AAS. The results showed that 0.1 M HCl was the best activator characterized by a decrease in % T of functional groups -OH, -CH and C-O which played an important role in the biosorption process, had the best Pb2+ metal biosorption capacity obtained from the AAS results, namely of 0.6462 mg/g with % biosorption 80.6239%.